O trágico em Édipo Rei e Lavoura Arcáica : leitura contrastiva - Gimenes, Thais Regina Pinheiro (2009)
This work discusses of the presence of tragic elements in the literary work of Oedipus the King and To the left of the father, as well as the sense of the tragic, under the works of Aristotle, Jean-Pierre Vernant and Pierre Vidal-Naquet, Northrop Frye, Marlies K. Danzinger and W. Stacy Johnson, Emil Staiger, Albin Lesky and Junito de Souza Brandão to mention some names. In order to do this, it was studied the text of Raduan Nassar, searching for examples in which it is possible to verify characterized aspects of the tragic, such as the ones presented in the Greek theater: excesses (hybris), tragic error (hamartia), cathartics or purgation effect (kátharsis), inversion of the situation of the personage (peripetéia), recognition (anagnórisis) and catastroph e(sparagmós). For a more practical result of the aimed objectives, we developed a contrasting reading between Oedipus the King, of Sófocles and To the left of the father, of Raduan Nassar, searching for elements where the sense of the tragic approaches or make Raduan´s speech distant from the tragic text of Sófocles. We used the comparative method, focusing on the concepts of Wellek (1958) and Carvalhal (1986), among others; the methodology implied the theory of textual interchangeability, based on Julia Kristeva (1974) concepts, the text seen as assimilation and rejoinder of another one (s), as a rewrite process. As a result, one has a differentiated reading of the romance of Raduan, offered by an approach of the traditional source of the classic tragedy.